Ecological Theology of Creation in The Perspective of The Theology of The Trinity - Jarosław Babiński (Studia Ecologiae et Bioethicae)
The action of God is always the action of the Trinity. Therefore, in properly interpreting theological issues, taking this truth into account is necessary. This is the reason for attempting to interpret the ecological theology of creation from a Trinitarian aspect. The analysis of biblical and theological sources provides the basis for this. The analyses carried out reconstruct the traditional issue model of the theology of creation. They develop an understanding of the relationship between God and creation. For the triune God is the model and deepest source of relationality. The essential love between the persons of the Trinity and the profound relationship of love between the Triune God and creation carries an inspiring message for the construction of man's relationship to the world according to God's design. This should constitute the essential foundation of an ecotheological praxeology.